Photocatalytic degradation of oxalic and dichloroacetic acid on TiO2 coated metal substrates - Ivanova, Irina (2013)
The photocatalytic activity of TiO2 immobilized on three different metal substrates (stainless steel, copper and titanium) has been investigated using dichloroacetic (DCA) and oxalic acid (OA) as model compounds. The TiO2 immobilization was realized by a novel process of Cold Spraying. The photocatalytic degradation experiments were performed in two cycles on every TiO2-coated metal substrate following two methodologies: (a) the same acid, i.e., OA or DCA, was degraded in the first and in the second cycle, and (b) one acid was used in the first cycle and the other acid in the second. OA was found to be more efficiently photocatalytically degraded than DCA; moreover, OA helps for the regeneration of the surface when employed after DCA. The use of copper as a substrate material was found to be photochemically active releasing basic species to the aqueous solution. Stainless steel and titanium are therefore less interfering choices to carry out mechanistic studies or, eventually, for environmental applications. The photonic efficiencies of the TiO2 particles immobilized on the three different metallic supports were compared to those found for TiO2 in an aqueous suspension. From the viewpoint of the amount of the employed photocatalyst, the TiO2-coated metal substrates are significantly more efficient for the degradation of OA than a highly efficient TiO2 suspension (Evonik P25), which content of nanoparticulate photocatalyst was enormously higher. Furthermore, OA and DCA can be completely mineralized at the supported catalyst